2016
DOI: 10.1002/anie.201510064
|View full text |Cite
|
Sign up to set email alerts
|

Remote‐Controlled Release of Singlet Oxygen by the Plasmonic Heating of Endoperoxide‐Modified Gold Nanorods: Towards a Paradigm Change in Photodynamic Therapy

Abstract: The photodynamic therapy of cancer is contingent upon the sustained generation of singlet oxygen in the tumor region. However, tumors of the most metastatic cancer types develop a region of severe hypoxia, which puts them beyond the reach of most therapeutic protocols. More troublesome, photodynamic action generates acute hypoxia as the process itself diminishes cellular oxygen reserves, which makes it a self-limiting method. Herein, we describe a new concept that could eventually lead to a change in the 100 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
124
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 33 publications
(33 reference statements)
2
124
0
1
Order By: Relevance
“…62 The target molecular system involved 9,10-diphenylanthracene EPO attached to the surface of gold nanorods through thiol linkers. Spectroscopic data revealed that each GNR carried approximately 6.5 × 10 9 endoperoxide molecules.…”
Section: Endoperoxides As a Source Of Singlet Oxygen For Hypoxic Tissmentioning
confidence: 99%
“…62 The target molecular system involved 9,10-diphenylanthracene EPO attached to the surface of gold nanorods through thiol linkers. Spectroscopic data revealed that each GNR carried approximately 6.5 × 10 9 endoperoxide molecules.…”
Section: Endoperoxides As a Source Of Singlet Oxygen For Hypoxic Tissmentioning
confidence: 99%
“…24 PDT has been developed in past decades, it is a promising modality for the management of various tumors and nonmalignant diseases, based on the application of photosensitizer (PS) and activated by a specific wavelength of light and resulted in photo damage and subsequent cell death via generating a lot of reactive oxygen species (ROS; such as hydrogen peroxide, hydroxyl radicals, and super oxides). [25][26][27] Herein, we report photo-activated nanoliposomes (PNLs) that impart photocytotoxicity to multiple tumor compartments and reversal of MDR and enable photoinitiated, rapid release of antitumor drugs ( Figure 1). As schemed in Figure 1, doxorubicin (DOX) was encapsulated in the hydrophilic inner chamber of nanoliposome, and a PS hematoporphyrin monomethyl ether (HMME) was embed in the phospholipid layer of nanoliposome.…”
mentioning
confidence: 99%
“…1 Many types of PS and PS-nanocarriers have been developed to overcome those limitations. 4 Integration with other oncologic interventions such as thermal therapies has been considered for synergistic photo cancer therapies. 5 …”
mentioning
confidence: 99%
“…4d,9 Various polymeric PS responding to internal and external stimuli such as pH, 10 enzymes, 11 and nucleic acid 12 have been actively studied. To this goal, conjugation of PS with thermosensitive polymers is an attractive strategy since it can improve PS solubility, control photoactivity, and enable combining PDT with thermal therapies.…”
mentioning
confidence: 99%